Green Sukuk And Green Banking: Strategic Collaboration For Islamic Sustainable Finance In Indonesia - Nadhifah, Tuti; Wahyuni, Desi; Risnawati, Heni; Thoha, Muhammad (BISNIS, 2026)
The global climate crisis necessitates a transformation of the financial sector toward environmentally sustainable practices. However, in Indonesia, the development of sharia-based green finance faces significant challenges, including unspecific regulations, low ESG literacy, and limited incentives for investors and market participants. This study discusses the potential and integration strategy of Green Sukuk and Green Banking as Islamic financial instruments that support sustainable financing. Green Sukuk acts as a source of financing for green projects in accordance with maqasid sharia principles, while Islamic banks implement Environmental, Social, and Governance (ESG) principles through green financing products and environmental literacy programs. This study highlights the importance of collaboration between regulators (OJK, DSN-MUI, KNEKS), Islamic banks, and capital markets to establish a regulatory framework that supports the development of Islamic green finance, including an Islamic green taxonomy and sharia-based ESG scoring. Despite obstacles such as unspecific regulations, low ESG literacy, and lack of fiscal incentives, the Sharia Green Investment Consortium collaboration model is proposed as an innovative solution to strengthen the Islamic green finance ecosystem. This research underscores the importance of policy synergy, human resource capacity building, and transparency in fund management to achieve sustainable development goals and increase the attractiveness of sharia-based green investments.